Airborne nitrogen deposition to the Baltic Sea: Past trends, source allocation and future projections. (15th May 2021) - Gauss, Michael; Bartnicki, Jerzy; Jalkanen, Jukka-Pekka; Nyiri, Agnes; Klein, Heiko; Fagerli, Hilde; Klimont, Zbigniew
Abstract: Despite significant reductions in nitrogen emissions achieved in Europe during the last three decades, eutrophication remains an environmental concern in the Baltic Sea basin. Recently, a number of comprehensive modelling studies have been conducted for the HELCOM Commission to inform the 2021 update of the Baltic Sea Action Plan. The calculations have focused on trends in airborne nitrogen deposition to the Baltic Sea and its nine sub-basins during the 2000–2017 period, the identification and ranking of the main contributors to deposition, as well as future projections for 2030, assuming compliance with the Gothenburg Protocol and the EU NEC Directive. This paper synthesizes the main results from these studies and puts them into the context of maximum allowable nutrient inputs to the Baltic Sea. According to our results, the airborne annual deposition to the Baltic Sea in 2017 amounted to 122.6 Gg(N) of oxidized nitrogen and 105.3 Gg(N) of reduced nitrogen, corresponding to a decrease since 2000 by, respectively, 39% and 11%. In order to filter out the large inter-annual variability due to meteorology and to better reflect trends in emissions, weather-normalized depositions of nitrogen have been calculated as well, according to which the decreases since 2000 amount to 35%, 7% and 25% for oxidized, reduced and total nitrogen, respectively. In 2017, Germany, Poland and Denmark were the most important contributors to airborne deposition of total (oxidized + reduced) nitrogen to the Baltic Sea. Agriculture contributed most to reduced nitrogen deposition, while the transport sector contributed most to oxidized nitrogen deposition. Agriculture in Germany was the single-most important contributor to nitrogen deposition to the Baltic Sea in 2017 (accounting for about 15% of the total), but there are numerous other important sectoral contributions. Emissions of nitrogen from the nine HELCOM Contracting Parties contributed 49%, 76% and 61% to oxidized, reduced and total nitrogen deposition, respectively. Assuming full compliance with the EU NEC Directive and the Gothenburg Protocol, significant further reductions in nitrogen deposition can be achieved by 2030, down to an annual deposition of 72.7 Gg(N) and 84.7 Gg(N) of oxidized and reduced nitrogen, respectively. Highlights: Airborne nitrogen deposition to the Baltic Sea has decreased since the 1990s, and this trend is projected to continue. Germany, Poland, and Denmark are the main contributors to nitrogen deposition to the Baltic Sea. Agriculture and transport are the main contributing sectors to nitrogen deposition to the Baltic Sea. Agreed emission abatement will lead to large reductions in oxidized nitrogen deposition to the Baltic Sea by 2030. Reductions in ammonia deposition by 2030 will be smaller, reflecting the smaller decrease in ammonia emissions by 2030.